2016
DOI: 10.1080/13621718.2015.1132127
|View full text |Cite
|
Sign up to set email alerts
|

Distortion and residual stresses in electron beam-welded hydroelectric turbine materials

Abstract: Heavy-section assembly of hydroelectric turbine runner materials using single-pass, autogenous EBW was demonstrated to penetrate a 90-mm-thick butt joint. The welding-induced distortions and residual stresses were characterised to understand the impact of the materials and process conditions (e.g. preheating and/or PWHT). Using 3D optical measurements, the angular distortions of EB-welded UNS S41500 and CA6NM steels were determined to be 0.13°and 0.38°, respectively. The longitudinal residual stresses, measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…is volumetric expansion then contributes significantly towards the development of compressive residual stresses and can compensate for the tensile residual stress transpiring from the accumulated thermal contraction strains due to EBW [38]. As the authors observed previously for as-welded CA6NM [11], the core FZ region in the heavy section weld can thus develop very high compressive residual stresses (− 500 MPa) relative to the HAZ that experiences high tensile residual stresses (600 MPa). During PWHT, stress relaxation mechanisms [39] reduce both the compressive and tensile residual stresses in the CA6NM EB weld.…”
Section: Residual Stress Distribution In Eb Welded Ca6nm Aftermentioning
confidence: 52%
See 1 more Smart Citation
“…is volumetric expansion then contributes significantly towards the development of compressive residual stresses and can compensate for the tensile residual stress transpiring from the accumulated thermal contraction strains due to EBW [38]. As the authors observed previously for as-welded CA6NM [11], the core FZ region in the heavy section weld can thus develop very high compressive residual stresses (− 500 MPa) relative to the HAZ that experiences high tensile residual stresses (600 MPa). During PWHT, stress relaxation mechanisms [39] reduce both the compressive and tensile residual stresses in the CA6NM EB weld.…”
Section: Residual Stress Distribution In Eb Welded Ca6nm Aftermentioning
confidence: 52%
“…e mechanical performance data generated for both materials indicated that the welds exhibited high strength and toughness [9,10] without PWHT. However, the residual stresses after EBW (∼600 MPa) CA6NM [11] were 110% of the YS of the alloy and greater than that recommended to prevent the initiation of unstable/premature failure. us, understanding the role of PWHT on the characteristics and properties of CA6NM EB welds is crucial for comprehensive assessment of the process feasibility to guide industrial practice for manufacturing low-carbon 13% Cr-4% Ni martensitic stainless steels.…”
Section: Introductionmentioning
confidence: 79%
“…The slitting method (Cheng and Finnie, 2007;Hill, 2013;Lee and Hill, 2007) was used to measure the thickness-averaged circumferential stress on a plane along the rolling direction (Pagliaro, 2008). A cross-sectional map of residual circumferential stress was measured on a plane along the transverse direction using the contour method (Hill and Olson, 2014;Hosseinzadeh and Bouchard, 2013;Kartal et al, 2016;Prime and DeWald, 2013;Sarafan et al, 2016;Withers et al, 2008;Xie et al, 2015;Zhang et al, 2003;Zhang et al, 2015), and the details for this specimen have been reported previously (Pagliaro et al, 2011). After the contour measurements, the radial stresses were measured on the exposed surface using x-ray diffraction and hole drilling, and superposition was…”
Section: Residual Stress and Strain Measurementsmentioning
confidence: 99%
“…Figure 10 shows a schematic of Goldak's model with its geometrical parameters: a and b for the lateral extent of the ellipsoid and its penetration depth, whereas c f and c r are the front and rear extents of the semi-ellipsoids, respectively. Equations [22] and [23] give the power density within the double-ellipsoid. [43]…”
Section: A Finite Element Model and Simulation Parametersmentioning
confidence: 99%
“…A volumetric expansion is associated with this transformation which induces compressive residual stresses. [20][21][22][23] Most studies on residual stress calculation in materials subjected to martensitic transformation during welding found in the literature [24][25][26][27] use the Koistinen-Marburger [28] (K-M) relation to address the austenite to martensite phase transformation problem. Since then, subsequently derived models have been proposed within the same framework.…”
Section: Introductionmentioning
confidence: 99%